How are children and adolescents cleaning their orthodontic appliances? A cross-sectional study in private schools - Mabel Miluska Suca Salas; Rita Regina Souza Lamas; Tatiana Pereira Cenci; Rafael Guerra Lund (Universidade Estadual de Campinas, 2015)
Aim: To determine the prevalence and the hygiene methods used by 6-16-year-old private school children and adolescents to clean removable orthodontic appliances (ROA) in the city of Pelotas, RS, Brazil. Methods: A cross-sectional study was conducted in private schools located in the urban area after the school tutors signed an informed consent form. Questionnaires were applied to children using removable orthodontic appliances. Data regarding hygiene methods of orthodontic appliances were collected. Descriptive analysis was performed. Pearson's chi-square test and Linear Trend with a confidence level of 95% were used for analytical analysis. Results: Children using ROA in private schools were 7.6%. The most frequent hygiene method used was mechanical cleansing with toothbrush and toothpaste (85.6%). Daily cleansing was the frequency most reported by children (51.6%). Conclusions: Use of ROA in students from private schools was low and the most used hygiene method was brushing with toothpaste.